PENGARUH IMPLEMENTASI SISTEM ADMINISTRASI KEPENDUDUKAN (SIAK) TERHADAP KUALITAS PELAYANAN ADMINISTRASI DI KECAMATAN JATINUNGGAL KEBUPATEN SUMEDANG - Mulia, Valdinni Sri (JRPA - Journal of Regional Public Administration, 2025)
The purpose of this study was to determine how well the Implementation of the Population Administration Information System (SIAK) and the Quality of Administrative Services in Jatinunggal District, to determine the relationship between the Implementation of the Population Administration Information System (SIAK) and the Quality of Administrative Services in Jatinunggal District, and to determine how much influence the Implementation of the Population Administration Information System (SIAK) and the Quality of Administrative Services in Jatinunggal District. This research uses descriptive analysis with a quantitative approach with non pobability sampling techniques with saturated sampling techniques. The number of samples studied was 35 respondents in Jatinunggal District, Sumedang Regency. The data analysis techniques used include presentation calculation, classical assumption test (data normality), correlation coefficient test with product moment, significant test and determination coefficient test.Based on the results of the study, it is known that the Implementation of the Population Administration Information System (SIAK) in Jatinunggal District is in very good criteria with a percentage value of 79.66%. Then for the Quality of Administrative Services in Jatinunggal District, amounting to 79.51%. From the results of the correlation analysis, a value of 0.904 was obtained and a significance value of 12,151 ≥ 1.681071 where this value indicates a positive and significant relationship between the Implementation of the Population Administration Information System (SIAK) and the Quality of Administrative Services in Jatinunggal District. From the results of the coefficient of determination analysis, it is known that the variables of the Implementation of the Population Administration Information System (SIAK) and the Quality of Administrative Services in Jatinunggal District, have a positive influence with a percentage value of 81.7% and the remaining 18.3% is influenced by other factors not examined in this model.